An Anthology of Philosophy in Persia. From the School of Shiraz to the Twentieth Century - Nasr, Seyyed Hossein, editor 266192; Razavi, Mehdi Amin, 1957-, editor 314682 (London ; New York : I.B. Tauris publishers : The Institute of Ismaili Studies, 2015)
Includes bibliographical and references